2016
DOI: 10.1371/journal.pone.0163347
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Healthcare Workers Self-Reported Practices, Knowledge and Attitude about Hand Hygiene in a Medical Setting in Rural India

Abstract: AimTo describe self-reported practices and assess knowledge and attitudes regarding hand hygiene among healthcare workers in a rural Indian teaching hospital.SettingA rural teaching hospital and its associated medical and nursing colleges in the district of Ujjain, India.MethodThe study population consisted of physicians, nurses, teaching staff, clinical instructors and nursing students. Self-administered questionnaires based on the World Health Organization Guidelines on Hand Hygiene in Healthcare were used.R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
36
2
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 41 publications
(54 reference statements)
1
36
2
3
Order By: Relevance
“…Lack of scientific information and the perception that priority is not given to hand hygiene, either on an individual or institutional level is a barrier to good hand hygiene practices (10). This was noted in our study were only 41% of observed participants wash their hands after patient examination or dressing.…”
Section: Discussionmentioning
confidence: 58%
“…Lack of scientific information and the perception that priority is not given to hand hygiene, either on an individual or institutional level is a barrier to good hand hygiene practices (10). This was noted in our study were only 41% of observed participants wash their hands after patient examination or dressing.…”
Section: Discussionmentioning
confidence: 58%
“…Other optional materials included 'Only water', 'Water and antiseptic solution' and 'Water and liquid soap. This study also showed the HCWs were willing to learn about hand hygiene in the future and willing to implement the same [11] . In resource limited countries the WHO manual on hand hygiene is not followed and a study shows that 17% of the doctors agreed that they were not aware of the manual [12] CONCLUSIONS Our hospital needs a proper hospital infection control team which should consist of a senior nurse as infection control nurse and a microbiologist.…”
Section: Various Hand Hygiene Products Usedmentioning
confidence: 63%
“…Similar results were shown in two studies conducted at general surgery department in Western India (26) and at a private tertiary healthcare hospital in Southern India (27), where third-generation cephalosporins were reported as the most commonly prescribed class of antibiotics. The preference to a broader spectrum antibiotic, such as the third-generation cephalosporin, might be due to the overall increase in prevalence of bacterial resistance to antibiotics in India that has been observed in other settings (4).De-escalation of antibiotic therapy is suggested for settings where broad-spectrum antibiotics are the first drug of choice, but was not found at our settings (28). Overall, nine out of ten patients who underwent clean-contaminated surgery were prescribed prophylactic antibiotic treatment for more than one day.…”
Section: Discussionmentioning
confidence: 73%
“…It is worth mentioning that the risk of SSI in clean surgery is reported to be less than 2% (22). Reasons to use a 'safety approach' could be a high patient burden per physician or presumed poor hygienic conditions of the patients as the catchment area included villages of low socio-economic status (28).All these presumptions need to be verified through a suggested qualitative study.…”
Section: Discussionmentioning
confidence: 99%